Preparation method of porous nano calcium silicate thermal insulation material

By using high-strength shells and toberymicolite nanosheets in porous nanocalcium silicate insulation materials, a complex pore network is formed using modified diatomaceous earth and glass fibers, which solves the insufficient insulation performance of existing materials. and the problem of low mechanical strength, efficient thermal insulation and structural stability are achieved.

CN119219388AActive Publication Date: 2024-12-31ZHEJIANG ASKER TECH
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202411762524.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2024-12-31
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

The existing preparation methods of porous calcium silicate insulation materials have problems such as insufficient insulation performance, low mechanical strength or complex preparation process, which are difficult to promote and apply on a large scale.

Method used

Using a combination of high-strength shell and toberymicolite nanosheets, a complex three-dimensional pore network structure is formed by treating modified diatomaceous earth, modified glass fibers and dispersants, thereby improving the porosity and dispersion of the material. and reduce thermal conductivity.

Benefits of technology

It significantly improves the insulation and mechanical properties of porous nano calcium silicate insulation materials, solves the deformation problem of traditional materials when temperature changes, simplifies the preparation process, and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of nano materials, in particular to a preparation method of a porous nano calcium silicate thermal insulation material. The preparation method comprises the following steps: preparation of a high-strength shell: uniformly mixing and stirring shell slurry consisting of hard calcium silicate fibers, high-alumina cement, quartz powder, modified diatomite, silicon dioxide, modified glass fibers and a dispersing agent, pouring the shell slurry into a mold, uniformly scraping, and drying and demolding at 100-110 DEG C, so as to obtain the high-strength shell, wherein the shell slurry is prepared from the hard calcium silicate fibers, the high-alumina cement, the quartz powder, the modified diatomite, the silicon dioxide, the modified glass fibers and the dispersing agent; pouring the mixed slurry into a mold, and pressurizing under the condition of 6-8MPa to obtain a wet blank; the wet blanks are stacked and fed into a drying kiln at the temperature of 250-260 DEG C to be dried, and then the product is obtained. According to the dispersing agent disclosed by the invention, porous structures of the modified diatomite and the modified glass fibers are interwoven with micropores of the hard calcium silicate fibers, so that a more complex three-dimensional pore network is formed. According to the structure, the porosity of the material is greatly increased, the heat conductivity is reduced, and therefore the heat preservation and insulation performance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nano materials, and in particular to a method for preparing a porous nano calcium silicate thermal insulation material. Background Art

[0002] With the rapid development of the construction industry and the increasing attention paid to energy efficiency, the performance requirements of thermal insulation materials, as an important part of building energy conservation, are also constantly improving. Porous nano calcium silicate thermal insulation materials have gradually become a popular product in the market due to their excellent thermal insulation performance, good mechanical strength and environmental protection characteristics.

[0003] The invention patent with the publication number CN117585976A discloses a method for preparing a composite nanoporous calcium silicate insulation material, comprising: using tetraethyl silicate, anhydrous ethanol, pure water and hydrochloric acid solution to prepare silica aerogel; composite the silica aerogel with xonotlite to prepare aerogel composite xonotlite; supercritically dry the aerogel composite xonotlite to obtain a nanoporous calcium silicate material; prepare nano calcium silicate slurry and nano calcium carbonate slurry to prepare a reinforced shell in a shell mold; use the prepared reinforced shell and the nanoporous calcium silicate material to prepare a finished composite nanoporous calcium silicate insulation material in a filter press mold. The present invention combines the insulation material with the strength-enhancing material to prepare a composite material, and applies this material in the preparation of the shell to obtain a composite material with excellent insulation performance and structural strength.

[0004] Although there are various preparation methods for porous calcium silicate thermal insulation materials, most of them have problems such as insufficient thermal insulation performance, low mechanical strength or complex preparation process. For example, traditional calcium silicate thermal insulation materials often adopt microporous structures, which have limited thermal insulation effects and are prone to deformation due to temperature changes during use. In addition, although some preparation methods can prepare calcium silicate materials with nanoporous structures, they often have disadvantages such as high preparation cost and complex process, which makes it difficult to promote and apply on a large scale. Based on this, the present invention proposes a preparation method for porous nano calcium silicate thermal insulation material. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a porous nano calcium silicate thermal insulation material, aiming to prepare a porous nano calcium silicate thermal insulation material with excellent thermal insulation performance.

[0006] The present invention provides a method for preparing a porous nano calcium silicate thermal insulation material, the steps comprising: (1) Preparation of high-strength shell: The shell slurry is composed of hard calcium silicate fiber, high-alumina cement, quartz powder, modified diatomaceous earth, silicon dioxide, modified glass fiber, and dispersant in a weight ratio of (20-30): (10-12): (20-24): (45-55): (10-16): (8-12): (4-6). The shell slurry is mixed and stirred evenly and poured into a mold, scraped evenly, and dried and demolded at 100-110°C to obtain the shell slurry; (2) Preparation of thermal insulation material: Tobermorite nanosheets, silica aerogel, silicone adhesive and hard calcium silicate fibers in a weight ratio of (10-12): (24-26): (2-3): (15-20) are mixed evenly to obtain a mixed slurry; a high-strength shell is laid in a filter press mold; the mixed slurry is poured into the mold and pressurized under a load of 6-8 MPa to obtain a wet blank; the wet blanks are stacked and sent to a drying kiln at 250-260°C for drying.

[0007] Furthermore, the preparation method of the hard calcium silicate fiber includes: adding water and powdered quartz at a CaO / SiO2 molar ratio of 0.9-0.97:1 and a water-to-material ratio of 18-24:1, stirring and mixing evenly, and then injecting into a dynamic reactor to generate needle-shaped or fibrous hard calcium silicate at 800-900°C.

[0008] Furthermore, the preparation method of the modified diatomite includes: first impregnating the diatomite with a sulfuric acid solution, washing it to neutrality for the first time, and drying it, then impregnating it with a sodium hydroxide solution, washing it to neutrality for the second time, and drying it, and then calcining the dried solid at a temperature of 550-600°C for 1-2h and grinding it to obtain the modified diatomite.

[0009] Furthermore, the mass concentration of the sulfuric acid solution is 10-12%, the immersion temperature of the sulfuric acid solution is 50-60° C., and the immersion time is 50-60 min.

[0010] Furthermore, the mass concentration of the sodium hydroxide solution is 6-8%, the immersion temperature of the sodium hydroxide solution is 35-45° C., and the immersion time is 30-40 min.

[0011] Furthermore, deionized water is used for both the first cleaning and the second cleaning; and the drying is vacuum drying at a drying temperature of 60-70°C.

[0012] Furthermore, the preparation method of the modified glass fiber includes: mixing alumina, silane coupling agent KH550, ethanol and deionized water, stirring for 2-3 hours at a temperature of 40-50°C to obtain a dispersion, then adding glass fiber, stirring for 4-5 hours at 200-300r / min, filtering and drying at a temperature of 50-60°C.

[0013] Furthermore, the weight ratio of the aluminum oxide, silane coupling agent KH550, ethanol, deionized water and glass fiber is (6-8): (0.4-0.5): (20-25): (15-20): (2-3).

[0014] Furthermore, the dispersant is sodium dodecylbenzene sulfonate, polyvinyl alcohol and deionized water in a weight ratio of (5-6): (8-10): (50-60).

[0015] Furthermore, the preparation method of the tobermorite nanosheets comprises: using silicon dioxide, calcium oxide and deionized water in a weight ratio of (1-2): (2-3): (6-8) as raw materials, ball-milling the mixed slurry, then performing a hydrothermal reaction in a reactor at a temperature of 220-240° C. to generate tobermorite slurry, placing the slurry in a ball mill equipped with an ultrasonic device, and using ultrasonic exfoliation to obtain ultrathin mesoporous nanosheets of 1.23 nm.

[0016] The beneficial effects of the present invention are: The modified diatomite in the present invention is treated alternately with sulfuric acid and sodium hydroxide to remove impurities and change the surface properties, thereby enhancing its performance as a filler. At the same time, the porous structure of the diatomite itself is retained or optimized during the modification process, further increasing the porosity of the material, which is beneficial to improving the thermal insulation effect. In addition, the modified diatomite, silicon dioxide and other components themselves have low thermal conductivity, and their distribution in the material further reduces the overall thermal conductivity and enhances the thermal insulation performance.

[0017] The modified glass fiber in the present invention is modified by aluminum oxide and a silane coupling agent to improve its dispersibility and bonding force in the matrix. The addition of glass fiber not only enhances the mechanical properties of the material, but also forms a three-dimensional network structure, which helps to fix and support the microporous structure of the hard calcium silicate fiber and the modified diatomaceous earth, and prevents the material from collapsing or deforming during use. The dispersibility and bonding of the modified glass fiber with the matrix are improved, which helps to form a more uniform pore distribution inside the material.

[0018] The dispersant in the present invention is a mixture of sodium dodecylbenzene sulfonate, polyvinyl alcohol and deionized water, which can effectively improve the dispersibility of each component in water and prevent the occurrence of agglomeration. This helps to form a uniform mixture during the preparation process and ensure the uniformity and stability of the internal structure of the material.

[0019] In addition, the dispersant makes the porous structure of modified diatomaceous earth and modified glass fiber intertwined with the micropores of hard calcium silicate fiber, forming a more complex three-dimensional pore network. This structure greatly increases the porosity of the material, reduces thermal conductivity, and thus improves thermal insulation performance. DETAILED DESCRIPTION

[0020] The technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. It should be noted that after the acid-base pretreatment of the modified diatomaceous earth, the diatomaceous earth is washed with deionized water to neutrality. Silica aerogel: Type I, ≥90% below 3 microns, ≥45% below 1 micron, Guangzhou People's Chemical Plant. Silicone adhesive: Dow Corning SE 9184. Example 1

[0021] This embodiment provides a method for preparing a porous nano calcium silicate thermal insulation material, the steps comprising: (1) Preparation of high-strength shell: The shell slurry is composed of hard calcium silicate fiber, high alumina cement, quartz powder, modified diatomaceous earth, silicon dioxide, modified glass fiber, and dispersant in a weight ratio of 25:11:22:50:13:10:5. The shell slurry is mixed and stirred evenly and poured into a mold, scraped evenly, and dried and demolded at 105°C. (2) Preparation of thermal insulation material: Tobermorite nanosheets, silica aerogel, silicone adhesive and hard calcium silicate fiber in a weight ratio of 11:25:2.5:17 are mixed evenly to obtain a mixed slurry; a high-strength shell is laid in a filter press mold; the mixed slurry is poured into the mold and pressurized under a load of 6-8 MPa to obtain a wet blank; the wet blanks are stacked and sent to a drying kiln at 255°C for drying.

[0022] Among them, the preparation method of the hard calcium silicate fiber includes: adding water and powdered quartz at a CaO / SiO2 molar ratio of 0.93:1 and a water-to-material ratio of 21:1, stirring and mixing evenly, and then injecting into a dynamic reactor to generate fibrous hard calcium silicate, i.e., hard calcium silicate fiber, at 850°C.

[0023] The preparation method of modified diatomite includes: firstly immersing the diatomite in a sulfuric acid solution with a mass concentration of 11% for 55 minutes at a temperature of 55°C, washing it to neutrality for the first time, and drying it under vacuum at 65°C for 22 hours, then immersing it in a sodium hydroxide solution with a mass concentration of 7% for 35 minutes at a temperature of 40°C, washing it to neutrality for the second time, and drying it under vacuum at 65°C for 22 hours, then calcining the dried solid at a temperature of 575°C for 1.5 hours, and grinding it to obtain the modified diatomite; The preparation method of the modified glass fiber includes: mixing aluminum oxide, silane coupling agent KH550, ethanol and deionized water, stirring at a temperature of 45°C for 2.5 hours to obtain a dispersion, then adding glass fiber, stirring at 250r / min for 4.5 hours, filtering and drying at a temperature of 55°C to obtain the dispersion; the weight ratio of aluminum oxide, silane coupling agent KH550, ethanol, deionized water and glass fiber is 7:0.45:22.5:17.5:2.5; The dispersant is sodium dodecylbenzene sulfonate, polyvinyl alcohol and deionized water in a weight ratio of 5.5:9:55; The preparation method of the tobermorite nanosheets includes: using silicon dioxide, calcium oxide and deionized water in a weight ratio of 1.5:2.5:7 as raw materials, ball-milling the mixed slurry, then performing a hydrothermal reaction in a reactor at a temperature of 230°C to generate tobermorite slurry, placing the slurry in a ball mill with ultrasonic equipment, and using ultrasonic peeling to obtain ultra-thin mesoporous nanosheets of 1.23 nm. Example 2

[0024] This embodiment provides a method for preparing a porous nano calcium silicate thermal insulation material, the steps comprising: (1) Preparation of high-strength shell: The shell slurry is composed of hard calcium silicate fiber, high alumina cement, quartz powder, modified diatomaceous earth, silicon dioxide, modified glass fiber, and dispersant in a weight ratio of 20:10:20:45:10:8:4. The shell slurry is mixed and stirred evenly and poured into a mold, scraped evenly, and dried and demolded at 100°C. (2) Preparation of thermal insulation material: Tobermorite nanosheets, silica aerogel, silicone adhesive and hard calcium silicate fiber in a weight ratio of 10:24:2:15 are mixed evenly to obtain a mixed slurry; a high-strength shell is laid in a filter press mold; the mixed slurry is poured into the mold and pressurized under a load of 6 MPa to obtain a wet blank; the wet blanks are stacked and sent to a drying kiln at 250°C for drying.

[0025] Among them, the preparation method of the hard calcium silicate fiber includes: adding water and powdered quartz at a CaO / SiO2 molar ratio of 0.9 and a water-to-material ratio of 18:1, stirring and mixing evenly, and then injecting into a dynamic reactor to generate fibrous hard calcium silicate, i.e., hard calcium silicate fiber, at 800°C.

[0026] The preparation method of modified diatomite includes: firstly immersing the diatomite in a sulfuric acid solution with a mass concentration of 10% for 50 minutes at a temperature of 50°C, washing it to neutrality for the first time, and drying it at 60°C in a vacuum for 20 hours, then immersing it in a sodium hydroxide solution with a mass concentration of 6% for 30 minutes at a temperature of 35°C, washing it to neutrality for the second time, and drying it at 60°C in a vacuum for 20 hours, then calcining the dried solid at a temperature of 550°C for 1 hour, and grinding it to obtain the modified diatomite; The preparation method of the modified glass fiber includes: mixing aluminum oxide, silane coupling agent KH550, ethanol and deionized water, stirring at a temperature of 40°C for 2 hours to obtain a dispersion, then adding glass fiber, stirring at 200r / min for 4 hours, filtering and drying at a temperature of 50°C to obtain the dispersion; the weight ratio of aluminum oxide, silane coupling agent KH550, ethanol, deionized water and glass fiber is 6:0.4:20:15:2; The dispersant is sodium dodecylbenzene sulfonate, polyvinyl alcohol and deionized water in a weight ratio of 5:8:50; The preparation method of the tobermorite nanosheets includes: using silicon dioxide, calcium oxide and deionized water in a weight ratio of 1:2:6 as raw materials, ball-milling the mixed slurry, then performing a hydrothermal reaction in a reactor at a temperature of 220°C to generate tobermorite slurry, placing the slurry in a ball mill with an ultrasonic device, and using ultrasonic peeling to obtain ultra-thin mesoporous nanosheets of 1.23 nm. Example 3

[0027] This embodiment provides a method for preparing a porous nano calcium silicate thermal insulation material, the steps comprising: (1) Preparation of high-strength shell: The shell slurry is composed of hard calcium silicate fiber, high alumina cement, quartz powder, modified diatomaceous earth, silicon dioxide, modified glass fiber, and dispersant in a weight ratio of 30:12:24:55:16:12:6. The shell slurry is mixed and stirred evenly and poured into a mold, scraped evenly, and dried and demolded at 110°C. (2) Preparation of thermal insulation material: Tobermorite nanosheets, silica aerogel, silicone adhesive and hard calcium silicate fiber in a weight ratio of 12:26:3:20 are mixed evenly to obtain a mixed slurry; a high-strength shell is laid in a filter press mold; the mixed slurry is poured into the mold and pressurized under a load of 8 MPa to obtain a wet blank; the wet blanks are stacked and sent to a drying kiln at 260°C for drying.

[0028] Among them, the preparation method of the hard calcium silicate fiber includes: adding water and powdered quartz at a CaO / SiO2 molar ratio of 0.97:1 and a water-to-material ratio of 24:1, stirring and mixing evenly, and then injecting into a dynamic reactor to generate fibrous hard calcium silicate, i.e., hard calcium silicate fiber, at 900°C.

[0029] The preparation method of modified diatomite includes: firstly immersing the diatomite in a sulfuric acid solution with a mass concentration of 12% for 60 minutes at a temperature of 60°C, washing it to neutrality for the first time, and drying it at 70°C in a vacuum for 24 hours, then immersing it in a sodium hydroxide solution with a mass concentration of 8% for 40 minutes at a temperature of 45°C, washing it to neutrality for the second time, and drying it at 70°C in a vacuum for 24 hours, then calcining the dried solid at a temperature of 600°C for 2 hours, and grinding it to obtain the modified diatomite; The preparation method of the modified glass fiber includes: mixing aluminum oxide, silane coupling agent KH550, ethanol and deionized water, stirring at a temperature of 50°C for 3 hours to obtain a dispersion, then adding glass fiber, stirring at 300r / min for 5 hours, filtering and drying at a temperature of 60°C to obtain the dispersion; the weight ratio of aluminum oxide, silane coupling agent KH550, ethanol, deionized water and glass fiber is 8:0.5:25:20:3; The dispersant is sodium dodecylbenzene sulfonate, polyvinyl alcohol and deionized water in a weight ratio of 6:10:60; The preparation method of the tobermorite nanosheets includes: using silicon dioxide, calcium oxide and deionized water in a weight ratio of 2:3:8 as raw materials, ball-milling the mixed slurry, then performing a hydrothermal reaction in a reactor at a temperature of 240°C to generate tobermorite slurry, placing the slurry in a ball mill with ultrasonic equipment, and using ultrasonic peeling to obtain ultra-thin mesoporous nanosheets of 1.23 nm. Example 4

[0030] This embodiment provides a method for preparing a porous nano calcium silicate thermal insulation material, the steps comprising: (1) Preparation of high-strength shell: The shell slurry is composed of hard calcium silicate fiber, high alumina cement, quartz powder, modified diatomaceous earth, silicon dioxide, modified glass fiber, and dispersant in a weight ratio of 20:12:20:55:10:12:4. The shell slurry is mixed and stirred evenly and poured into a mold, scraped evenly, and dried and demolded at 110°C. (2) Preparation of thermal insulation material: Tobermorite nanosheets, silica aerogel, silicone adhesive and hard calcium silicate fiber in a weight ratio of 10:26:2:20 are mixed evenly to obtain a mixed slurry; a high-strength shell is laid in a filter press mold; the mixed slurry is poured into the mold and pressurized under a load of 6 MPa to obtain a wet blank; the wet blanks are stacked and sent to a drying kiln at 260°C for drying.

[0031] Among them, the preparation method of the hard calcium silicate fiber includes: adding water and powdered quartz at a CaO / SiO2 molar ratio of 0.9:1 and a water-to-material ratio of 24:1, stirring and mixing evenly, and then injecting into a dynamic reactor to generate fibrous hard calcium silicate, i.e., hard calcium silicate fiber, at 800°C.

[0032] The preparation method of modified diatomite includes: firstly immersing the diatomite in a sulfuric acid solution with a mass concentration of 10% for 60 minutes at a temperature of 50°C, washing it to neutrality for the first time, and drying it under vacuum at 70°C for 20 hours, then immersing it in a sodium hydroxide solution with a mass concentration of 8% for 30 minutes at a temperature of 45°C, washing it to neutrality for the second time, and drying it under vacuum at 60°C for 24 hours, then calcining the dried solid at a temperature of 550°C for 2 hours, and grinding it to obtain the modified diatomite; The preparation method of the modified glass fiber includes: mixing aluminum oxide, silane coupling agent KH550, ethanol and deionized water, stirring at a temperature of 40°C for 3 hours to obtain a dispersion, then adding glass fiber, stirring at 200r / min for 5 hours, filtering and drying at a temperature of 50°C to obtain the dispersion; the weight ratio of aluminum oxide, silane coupling agent KH550, ethanol, deionized water and glass fiber is 8:0.4:25:15:3; The dispersant is sodium dodecylbenzene sulfonate, polyvinyl alcohol and deionized water in a weight ratio of 5:10:50; The preparation method of the tobermorite nanosheets includes: using silicon dioxide, calcium oxide and deionized water in a weight ratio of 1:3:6 as raw materials, ball-milling the mixed slurry, then performing a hydrothermal reaction in a reactor at a temperature of 220°C to generate tobermorite slurry, placing the slurry in a ball mill with ultrasonic equipment, and using ultrasonic peeling to obtain ultra-thin mesoporous nanosheets of 1.23 nm.

[0033] Comparative Example 1 This comparative example provides a method for preparing a porous nano calcium silicate thermal insulation material, the steps comprising: (1) Preparation of high-strength shell: The shell slurry is composed of hard calcium silicate fiber, high alumina cement, quartz powder, modified diatomaceous earth, silicon dioxide, modified glass fiber, and dispersant in a weight ratio of 25:11:22:50:13:10:5. The shell slurry is mixed and stirred evenly and poured into a mold, scraped evenly, and dried and demolded at 105°C. (2) Preparation of thermal insulation material: Tobermorite nanosheets, silica aerogel, silicone adhesive and hard calcium silicate fiber in a weight ratio of 11:25:2.5:17 are mixed evenly to obtain a mixed slurry; a high-strength shell is laid in a filter press mold; the mixed slurry is poured into the mold and pressurized under a load of 6-8 MPa to obtain a wet blank; the wet blanks are stacked and sent to a drying kiln at 255°C for drying.

[0034] Among them, the preparation method of the hard calcium silicate fiber includes: adding water and powdered quartz at a CaO / SiO2 molar ratio of 0.93:1 and a water-to-material ratio of 21:1, stirring and mixing evenly, and then injecting into a dynamic reactor to generate fibrous hard calcium silicate, i.e., hard calcium silicate fiber, at 850°C.

[0035] The preparation method of modified diatomite includes: impregnating diatomite with a sodium hydroxide solution with a mass concentration of 7% for 35 minutes at a temperature of 40°C, washing to neutrality, drying under vacuum at 65°C for 22 hours, and then calcining the dried solid at a temperature of 575°C for 1.5 hours, and grinding to obtain the modified diatomite; The preparation method of the modified glass fiber includes: mixing aluminum oxide, silane coupling agent KH550, ethanol and deionized water, stirring at a temperature of 45°C for 2.5 hours to obtain a dispersion, then adding glass fiber, stirring at 250r / min for 4.5 hours, filtering and drying at a temperature of 55°C to obtain the dispersion; the weight ratio of aluminum oxide, silane coupling agent KH550, ethanol, deionized water and glass fiber is 7:0.45:22.5:17.5:2.5; The dispersant is sodium dodecylbenzene sulfonate, polyvinyl alcohol and deionized water in a weight ratio of 5.5:9:55; The preparation method of the tobermorite nanosheets includes: using silicon dioxide, calcium oxide and deionized water in a weight ratio of 1.5:2.5:7 as raw materials, ball-milling the mixed slurry, then performing a hydrothermal reaction in a reactor at a temperature of 230°C to generate tobermorite slurry, placing the slurry in a ball mill with ultrasonic equipment, and using ultrasonic peeling to obtain ultra-thin mesoporous nanosheets of 1.23 nm.

[0036] Comparative Example 2 This comparative example provides a method for preparing a porous nano calcium silicate thermal insulation material, the steps comprising: (1) Preparation of high-strength shell: The shell slurry is composed of hard calcium silicate fiber, high alumina cement, quartz powder, modified diatomaceous earth, silicon dioxide, modified glass fiber, and dispersant in a weight ratio of 25:11:22:50:13:10:5. The shell slurry is mixed and stirred evenly and poured into a mold, scraped evenly, and dried and demolded at 105°C. (2) Preparation of thermal insulation material: Tobermorite nanosheets, silica aerogel, silicone adhesive and hard calcium silicate fiber in a weight ratio of 11:25:2.5:17 are mixed evenly to obtain a mixed slurry; a high-strength shell is laid in a filter press mold; the mixed slurry is poured into the mold and pressurized under a load of 6-8 MPa to obtain a wet blank; the wet blanks are stacked and sent to a drying kiln at 255°C for drying.

[0037] Among them, the preparation method of the hard calcium silicate fiber includes: adding water and powdered quartz at a CaO / SiO2 molar ratio of 0.93:1 and a water-to-material ratio of 21:1, stirring and mixing evenly, and then injecting into a dynamic reactor to generate fibrous hard calcium silicate, i.e., hard calcium silicate fiber, at 850°C.

[0038] The preparation method of modified diatomite includes: firstly immersing the diatomite in a sulfuric acid solution with a mass concentration of 11% for 55 minutes at a temperature of 55°C, washing it to neutrality for the first time, drying it under vacuum at 65°C for 22 hours, then calcining the dried solid at a temperature of 575°C for 1.5 hours, and grinding it to obtain the modified diatomite; The preparation method of the modified glass fiber includes: mixing aluminum oxide, silane coupling agent KH550, ethanol and deionized water, stirring at a temperature of 45°C for 2.5 hours to obtain a dispersion, then adding glass fiber, stirring at 250r / min for 4.5 hours, filtering and drying at a temperature of 55°C to obtain the dispersion; the weight ratio of aluminum oxide, silane coupling agent KH550, ethanol, deionized water and glass fiber is 7:0.45:22.5:17.5:2.5; The dispersant is sodium dodecylbenzene sulfonate, polyvinyl alcohol and deionized water in a weight ratio of 5.5:9:55; The preparation method of the tobermorite nanosheets includes: using silicon dioxide, calcium oxide and deionized water in a weight ratio of 1.5:2.5:7 as raw materials, ball-milling the mixed slurry, then performing a hydrothermal reaction in a reactor at a temperature of 230°C to generate tobermorite slurry, placing the slurry in a ball mill with ultrasonic equipment, and using ultrasonic peeling to obtain ultra-thin mesoporous nanosheets of 1.23 nm.

[0039] Comparative Example 3 This comparative example provides a method for preparing a porous nano calcium silicate thermal insulation material, the steps comprising: (1) Preparation of high-strength shell: The shell slurry is composed of hard calcium silicate fiber, high alumina cement, quartz powder, diatomaceous earth, silicon dioxide, modified glass fiber, and dispersant in a weight ratio of 25:11:22:50:13:10:5. The shell slurry is mixed and stirred evenly and poured into a mold, scraped evenly, and dried and demolded at 105°C. (2) Preparation of thermal insulation material: Tobermorite nanosheets, silica aerogel, silicone adhesive and hard calcium silicate fiber in a weight ratio of 11:25:2.5:17 are mixed evenly to obtain a mixed slurry; a high-strength shell is laid in a filter press mold; the mixed slurry is poured into the mold and pressurized under a load of 6-8 MPa to obtain a wet blank; the wet blanks are stacked and sent to a drying kiln at 255°C for drying.

[0040] Among them, the preparation method of the hard calcium silicate fiber includes: adding water and powdered quartz at a CaO / SiO2 molar ratio of 0.93:1 and a water-to-material ratio of 21:1, stirring and mixing evenly, and then injecting into a dynamic reactor to generate fibrous hard calcium silicate, i.e., hard calcium silicate fiber, at 850°C.

[0041] The preparation method of the modified glass fiber includes: mixing aluminum oxide, silane coupling agent KH550, ethanol and deionized water, stirring at a temperature of 45°C for 2.5 hours to obtain a dispersion, then adding glass fiber, stirring at 250r / min for 4.5 hours, filtering and drying at a temperature of 55°C to obtain the dispersion; the weight ratio of aluminum oxide, silane coupling agent KH550, ethanol, deionized water and glass fiber is 7:0.45:22.5:17.5:2.5; The dispersant is sodium dodecylbenzene sulfonate, polyvinyl alcohol and deionized water in a weight ratio of 5.5:9:55; The preparation method of the tobermorite nanosheets includes: using silicon dioxide, calcium oxide and deionized water in a weight ratio of 1.5:2.5:7 as raw materials, ball-milling the mixed slurry, then performing a hydrothermal reaction in a reactor at a temperature of 230°C to generate tobermorite slurry, placing the slurry in a ball mill with ultrasonic equipment, and using ultrasonic peeling to obtain ultra-thin mesoporous nanosheets of 1.23 nm.

[0042] Comparative Example 4 This comparative example provides a method for preparing a porous nano calcium silicate thermal insulation material, the steps comprising: (1) Preparation of high-strength shell: The shell slurry is composed of hard calcium silicate fiber, high alumina cement, quartz powder, silicon dioxide, modified glass fiber, and dispersant in a weight ratio of 25:11:22:13:10:5. The shell slurry is mixed and stirred evenly and poured into a mold, scraped evenly, and dried and demolded at 105°C. (2) Preparation of thermal insulation material: Tobermorite nanosheets, silica aerogel, silicone adhesive and hard calcium silicate fiber in a weight ratio of 11:25:2.5:17 are mixed evenly to obtain a mixed slurry; a high-strength shell is laid in a filter press mold; the mixed slurry is poured into the mold and pressurized under a load of 6-8 MPa to obtain a wet blank; the wet blanks are stacked and sent to a drying kiln at 255°C for drying.

[0043] Among them, the preparation method of the hard calcium silicate fiber includes: adding water and powdered quartz at a CaO / SiO2 molar ratio of 0.93:1 and a water-to-material ratio of 21:1, stirring and mixing evenly, and then injecting into a dynamic reactor to generate fibrous hard calcium silicate, i.e., hard calcium silicate fiber, at 850°C.

[0044] The preparation method of the modified glass fiber includes: mixing aluminum oxide, silane coupling agent KH550, ethanol and deionized water, stirring at a temperature of 45°C for 2.5 hours to obtain a dispersion, then adding glass fiber, stirring at 250r / min for 4.5 hours, filtering and drying at a temperature of 55°C to obtain the dispersion; the weight ratio of aluminum oxide, silane coupling agent KH550, ethanol, deionized water and glass fiber is 7:0.45:22.5:17.5:2.5; The dispersant is sodium dodecylbenzene sulfonate, polyvinyl alcohol and deionized water in a weight ratio of 5.5:9:55; The preparation method of the tobermorite nanosheets includes: using silicon dioxide, calcium oxide and deionized water in a weight ratio of 1.5:2.5:7 as raw materials, ball-milling the mixed slurry, then performing a hydrothermal reaction in a reactor at a temperature of 230°C to generate tobermorite slurry, placing the slurry in a ball mill with ultrasonic equipment, and using ultrasonic peeling to obtain ultra-thin mesoporous nanosheets of 1.23 nm.

[0045] Comparative Example 5 This comparative example provides a method for preparing a porous nano calcium silicate thermal insulation material, the steps comprising: (1) Preparation of high-strength shell: The shell slurry is composed of hard calcium silicate fiber, high alumina cement, quartz powder, modified diatomaceous earth, silicon dioxide, glass fiber, and dispersant in a weight ratio of 25:11:22:50:13:10:5. The shell slurry is mixed and stirred evenly and poured into a mold, scraped evenly, and dried and demolded at 105°C. (2) Preparation of thermal insulation material: Tobermorite nanosheets, silica aerogel, silicone adhesive and hard calcium silicate fiber in a weight ratio of 11:25:2.5:17 are mixed evenly to obtain a mixed slurry; a high-strength shell is laid in a filter press mold; the mixed slurry is poured into the mold and pressurized under a load of 6-8 MPa to obtain a wet blank; the wet blanks are stacked and sent to a drying kiln at 255°C for drying.

[0046] Among them, the preparation method of the hard calcium silicate fiber includes: adding water and powdered quartz at a CaO / SiO2 molar ratio of 0.93:1 and a water-to-material ratio of 21:1, stirring and mixing evenly, and then injecting into a dynamic reactor to generate fibrous hard calcium silicate, i.e., hard calcium silicate fiber, at 850°C.

[0047] The preparation method of modified diatomite includes: firstly immersing the diatomite in a sulfuric acid solution with a mass concentration of 11% for 55 minutes at a temperature of 55°C, washing it to neutrality for the first time, and drying it under vacuum at 65°C for 22 hours, then immersing it in a sodium hydroxide solution with a mass concentration of 7% for 35 minutes at a temperature of 40°C, washing it to neutrality for the second time, and drying it under vacuum at 65°C for 22 hours, then calcining the dried solid at a temperature of 575°C for 1.5 hours, and grinding it to obtain the modified diatomite; The dispersant is sodium dodecylbenzene sulfonate, polyvinyl alcohol and deionized water in a weight ratio of 5.5:9:55; The preparation method of the tobermorite nanosheets includes: using silicon dioxide, calcium oxide and deionized water in a weight ratio of 1.5:2.5:7 as raw materials, ball-milling the mixed slurry, then performing a hydrothermal reaction in a reactor at a temperature of 230°C to generate tobermorite slurry, placing the slurry in a ball mill with ultrasonic equipment, and using ultrasonic peeling to obtain ultra-thin mesoporous nanosheets of 1.23 nm.

[0048] Comparative Example 6 This comparative example provides a method for preparing a porous nano calcium silicate thermal insulation material, the steps comprising: (1) Preparation of high-strength shell: The shell slurry is composed of hard calcium silicate fiber, high-alumina cement, quartz powder, modified diatomaceous earth, and silicon dioxide dispersant in a weight ratio of 25:11:22:50:13:5. The shell slurry is mixed and stirred evenly and poured into a mold, scraped evenly, and dried and demolded at 105°C. (2) Preparation of thermal insulation material: Tobermorite nanosheets, silica aerogel, silicone adhesive and hard calcium silicate fiber in a weight ratio of 11:25:2.5:17 are mixed evenly to obtain a mixed slurry; a high-strength shell is laid in a filter press mold; the mixed slurry is poured into the mold and pressurized under a load of 6-8 MPa to obtain a wet blank; the wet blanks are stacked and sent to a drying kiln at 255°C for drying.

[0049] Among them, the preparation method of the hard calcium silicate fiber includes: adding water and powdered quartz at a CaO / SiO2 molar ratio of 0.93:1 and a water-to-material ratio of 21:1, stirring and mixing evenly, and then injecting into a dynamic reactor to generate fibrous hard calcium silicate, i.e., hard calcium silicate fiber, at 850°C.

[0050] The preparation method of modified diatomite includes: firstly immersing the diatomite in a sulfuric acid solution with a mass concentration of 11% for 55 minutes at a temperature of 55°C, washing it to neutrality for the first time, and drying it under vacuum at 65°C for 22 hours, then immersing it in a sodium hydroxide solution with a mass concentration of 7% for 35 minutes at a temperature of 40°C, washing it to neutrality for the second time, and drying it under vacuum at 65°C for 22 hours, then calcining the dried solid at a temperature of 575°C for 1.5 hours, and grinding it to obtain the modified diatomite; The dispersant is sodium dodecylbenzene sulfonate, polyvinyl alcohol and deionized water in a weight ratio of 5.5:9:55; The preparation method of the tobermorite nanosheets includes: using silicon dioxide, calcium oxide and deionized water in a weight ratio of 1.5:2.5:7 as raw materials, ball-milling the mixed slurry, then performing a hydrothermal reaction in a reactor at a temperature of 230°C to generate tobermorite slurry, placing the slurry in a ball mill with ultrasonic equipment, and using ultrasonic peeling to obtain ultra-thin mesoporous nanosheets of 1.23 nm.

[0051] Comparative Example 7 This comparative example provides a method for preparing a porous nano calcium silicate thermal insulation material, the steps comprising: (1) Preparation of high-strength shell: The shell slurry is composed of hard calcium silicate fiber, high alumina cement, quartz powder, modified diatomaceous earth, silicon dioxide, modified glass fiber, and dispersant in a weight ratio of 25:11:22:50:13:10:5. The shell slurry is mixed and stirred evenly and poured into a mold, scraped evenly, and dried and demolded at 105°C. (2) Preparation of thermal insulation material: Tobermorite nanosheets, silica aerogel, silicone adhesive and hard calcium silicate fiber in a weight ratio of 11:25:2.5:17 are mixed evenly to obtain a mixed slurry; a high-strength shell is laid in a filter press mold; the mixed slurry is poured into the mold and pressurized under a load of 6-8 MPa to obtain a wet blank; the wet blanks are stacked and sent to a drying kiln at 255°C for drying.

[0052] Among them, the preparation method of the hard calcium silicate fiber includes: adding water and powdered quartz at a CaO / SiO2 molar ratio of 0.93:1 and a water-to-material ratio of 21:1, stirring and mixing evenly, and then injecting into a dynamic reactor to generate fibrous hard calcium silicate, i.e., hard calcium silicate fiber, at 850°C.

[0053] The preparation method of modified diatomite includes: firstly immersing the diatomite in a sulfuric acid solution with a mass concentration of 11% for 55 minutes at a temperature of 55°C, washing it to neutrality for the first time, and drying it under vacuum at 65°C for 22 hours, then immersing it in a sodium hydroxide solution with a mass concentration of 7% for 35 minutes at a temperature of 40°C, washing it to neutrality for the second time, and drying it under vacuum at 65°C for 22 hours, then calcining the dried solid at a temperature of 575°C for 1.5 hours, and grinding it to obtain the modified diatomite; The preparation method of the modified glass fiber includes: mixing aluminum oxide, silane coupling agent KH550, ethanol and deionized water, stirring at a temperature of 45°C for 2.5 hours to obtain a dispersion, then adding glass fiber, stirring at 250r / min for 4.5 hours, filtering and drying at a temperature of 55°C to obtain the dispersion; the weight ratio of aluminum oxide, silane coupling agent KH550, ethanol, deionized water and glass fiber is 7:0.45:22.5:17.5:2.5; The dispersant is polyvinyl alcohol and deionized water in a weight ratio of 9:55; The preparation method of the tobermorite nanosheets includes: using silicon dioxide, calcium oxide and deionized water in a weight ratio of 1.5:2.5:7 as raw materials, ball-milling the mixed slurry, then performing a hydrothermal reaction in a reactor at a temperature of 230°C to generate tobermorite slurry, placing the slurry in a ball mill with ultrasonic equipment, and using ultrasonic peeling to obtain ultra-thin mesoporous nanosheets of 1.23 nm.

[0054] The porous nano calcium silicate thermal insulation materials prepared in Examples 1-4 and Comparative Examples 1-7 were tested, and the results are shown in Table 1 below.

[0055] Table 1: Performance Test

[0056] Finally, it should be noted that: the applicant declares that the present invention uses the above-mentioned embodiments to illustrate the products and detailed preparation methods of the present invention, but the present invention is not limited to the above-mentioned products and detailed preparation methods, that is, it does not mean that the present invention must rely on the above-mentioned products and detailed preparation methods to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials of the products of the present invention and the addition of auxiliary materials, the selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

[0057] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited to the specific details in the above embodiments, and the technical solution of the present invention can be subjected to a variety of simple modifications within the technical concept of the present invention. These simple modifications all belong to the protection scope of the present invention.

[0058] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0059] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A method for preparing a porous nano calcium silicate thermal insulation material, characterized in that the steps include: (1) Preparation of high-strength shell: The shell slurry is composed of hard calcium silicate fiber, high-alumina cement, quartz powder, modified diatomaceous earth, silicon dioxide, modified glass fiber, and dispersant in a weight ratio of (20-30): (10-12): (20-24): (45-55): (10-16): (8-12): (4-6). The shell slurry is mixed and stirred evenly and poured into a mold, scraped evenly, and dried and demolded at 100-110°C to obtain the shell slurry; (2) Preparation of thermal insulation material: Tobermorite nanosheets, silica aerogel, silicone adhesive and hard calcium silicate fibers in a weight ratio of (10-12): (24-26): (2-3): (15-20) are uniformly stirred to obtain a mixed slurry; a high-strength shell is laid in a filter press mold; the mixed slurry is poured into the mold and pressurized under a load of 6-8 MPa to obtain a wet blank; The wet blanks are stacked and sent into a drying kiln at 250-260℃ for drying.

2. The method for preparing a porous nano calcium silicate thermal insulation material according to claim 1, characterized in that: The preparation method of the hard calcium silicate fiber comprises: adding water and powdered quartz at a CaO / SiO2 molar ratio of 0.9-0.97:1 and a water-to-material ratio of 18-24:1, stirring and mixing evenly, and then injecting into a dynamic reactor to generate needle-shaped or fibrous hard calcium silicate at 800-900°C.

3. The method for preparing a porous nano calcium silicate thermal insulation material according to claim 1, characterized in that: The preparation method of the modified diatomite comprises: firstly impregnating the diatomite with a sulfuric acid solution, washing it to neutrality for the first time, and drying it, then impregnating it with a sodium hydroxide solution, washing it to neutrality for the second time, and drying it, then calcining the dried solid at a temperature of 550-600° C. for 1-2 hours, and grinding it to obtain the modified diatomite.

4. The method for preparing a porous nano calcium silicate thermal insulation material according to claim 3, characterized in that: The mass concentration of the sulfuric acid solution is 10-12%, the immersion temperature of the sulfuric acid solution is 50-60° C., and the immersion time is 50-60 min.

5. The method for preparing a porous nano calcium silicate thermal insulation material according to claim 3, characterized in that: The mass concentration of the sodium hydroxide solution is 6-8%, the immersion temperature of the sodium hydroxide solution is 35-45° C., and the immersion time is 30-40 minutes.

6. The method for preparing a porous nano calcium silicate thermal insulation material according to claim 3, characterized in that: Deionized water is used for both the first and second washings; the drying is vacuum drying, the drying temperature is 60-70° C., and the drying time is 20-24 hours.

7. The method for preparing a porous nano calcium silicate thermal insulation material according to claim 1, characterized in that: The preparation method of the modified glass fiber comprises: mixing alumina, silane coupling agent KH550, ethanol and deionized water, stirring for 2-3 hours at a temperature of 40-50° C. to obtain a dispersion, then adding glass fiber, stirring for 4-5 hours at a speed of 200-300 r / min, filtering and drying at a temperature of 50-60° C. to obtain the dispersion.

8. The method for preparing a porous nano calcium silicate thermal insulation material according to claim 7, characterized in that: The weight ratios of the aluminum oxide, the silane coupling agent KH550, the ethanol, the deionized water and the glass fiber are (6-8): (0.4-0.5): (20-25): (15-20): (2-3).

9. The method for preparing a porous nano calcium silicate thermal insulation material according to claim 1, characterized in that: The dispersant is sodium dodecylbenzene sulfonate, polyvinyl alcohol and deionized water in a weight ratio of (5-6): (8-10): (50-60).

10. The method for preparing a porous nano calcium silicate thermal insulation material according to claim 1, characterized in that: The preparation method of the tobermorite nanosheets comprises: using silicon dioxide, calcium oxide and deionized water in a weight ratio of (1-2): (2-3): (6-8) as raw materials, ball-milling the mixed slurry, then performing a hydrothermal reaction in a reactor at a temperature of 220-240° C. to generate tobermorite slurry, placing the slurry in a ball mill equipped with an ultrasonic device, and using ultrasonic peeling to obtain ultrathin mesoporous nanosheets of 1.23 nm.

Citation Information

Patent Citations

  • High-thermal-conductivity ceramic base plate and manufacturing method thereof

    CN107602095A

  • Preparation method of multi-fiber-reinforced gypsum-based composite material

    CN107879692A

  • Ultralight high-temperature calcium silicate heat-insulating product composition and preparation method thereof

    CN108793942A

  • Heat insulation material for building and preparation method thereof

    CN109761539A

  • High-performance anti-freezing concrete and preparation method thereof

    CN112174610A